The primary grasslands of the northern Apennine summits (N-Italy): a phytosociological and ecological survey - Marcello Tomaselli; Michele Carbognani; Bruno Foggi; Alessandro Petraglia; Graziano Rossi; Leonardo Lombardi; Matilde Gennai (2019)
This paper provides a comprehensive phytosociological survey on the alpine grasslands occurring on the northern Apennine summits (N-Italy). The study area represents a crucial phytogeographic joint between the Alps and the Apennines and its summit grassland vegetation was only partially document-ed at the time. Research was based on 219 relevés classified combining a preliminary manual procedure with a cluster analysis that was performed with the Ward’s minimum variance method on the chord distance matrix. In such a way, six different plant associations were identified and allocated to three different phytosociological classes (Juncetea trifidi, Elyno-Seslerietea, Carici rupestris-Kobresieteabellardii). All the six associations could be regarded as endemic because occurring only in the study area. Four of them were described here for the first time and typified according to the rules of the Inter-national Code of Phytosociological Nomenclature. The relevés corresponding to calcium-poor grass-lands (Juncetea trifidi) were assigned to three different associations allocated to the suballiance Festucenion riccerii, here newly described. The relevés corresponding to calcium-rich grasslands (Elyno-Seslerietea) were assigned to two associations, respectively, belonging to the alliance Caricion ferrugineae and to a new alliance described here under the name Caricion sempervirentis-Seslerionapenninae. Finally, a graminoid tundra association was firstly documented for the northern Apennines and assigned to the alliance Oxytropido-Elynion myosuroidis. The extent and quality of species fidelity to the different plant associations was detected by developing a metric named “Retention Index” (RIN). Calculation of RIN values showed that calcium-rich grasslands retained a higher floristic distinctive-ness with respect to the calcium-poor ones. The analysis of environmental gradients within the grass-land vegetation was performed through Principal Component Analysis (PCA), adopting Ellenberg indicator values as indirect ...